Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Geomechanical modeling and slip and dilation tendency analysis track stress evolution during geothermal energy extraction - Kevin J. Smart; David A. Ferrill; Adam J. Cawood (Journal of Structural Geology, 2026)

I lost my number, can I have yours? Body image satisfaction with sexually dimorphic traits is associated with men's dating anxiety and confidence - David A. Frederick; Tania A. Reynolds; Nikoline L. Smart; Justin R. Garcia; David A. Puts (Evolution and Human Behavior, 2026)

Fault and fracture response to Neogene extension in the western Delaware Basin, Texas - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Bethany Rysak Bryce; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2026)

Hyperspectral remote sensing for monitoring coral reef and seagrass Ecosystems: capabilities, limitations and future directions - Joanna N. Smart; Dylan Cowley; David E. Carrasco Rivera; Muhammed Hafizt; Mitchell Lyons; Stuart Phinn; Chris Roelfsema (Marine Environmental Research, 2026)

Erratum to “Varying response of breeding waders to experimental manipulation of their habitat and predators” [J. Nat. Conserv. 72 (2023) 126353] - David J.T. Douglas; Irena Tománková; Philippa Gullett; Stephen G. Dodd; Daniel Brown; Martin Clift; Norrie Russell; Neal Warnock; Jennifer Smart; Sarah Sanders (Journal for Nature Conservation, 2026)

Fault zone deformation and fracture intensity in chalk-dominated carbonates - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2025)

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Fracturing in basinal siliciclastic deposits of the Wolfcampian Alta Formation, Marfa Basin, west Texas - David A. Ferrill; Kevin J. Smart; Adam J. Cawood; Daniel J. Lehrmann; Giovanni Zanoni; R. Ryan King (Marine and Petroleum Geology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Corrigendum to “Evidence for regional ﬂuid migration in the Eagle Ford Formation, Austin Chalk, and Buda Limestone of south-central and west Texas, USA” [Mar. Petrol. Geol. 166 (2024) 106896] - Mark A. Evans; David A. Ferrill; Kevin J. Smart (Marine and Petroleum Geology, 2024)

Evidence for regional fluid migration in the Eagle Ford Formation, Austin Chalk, and Buda Limestone of south-central and west Texas, USA - Mark A. Evans; David A. Ferrill; Kevin J. Smart (Marine and Petroleum Geology, 2024)

Thrust v. stylolite - David A. Ferrill; Adam J. Cawood; Mark A. Evans; Kevin J. Smart; R. Ryan King; Giovanni Zanoni (Journal of Structural Geology, 2024)

Multi-endpoint in vitro toxicological assessment of snus and tobacco-free nicotine pouch extracts - Fan Yu; Emma Bishop; Fabio Miazzi; Rhian Evans; David Smart; Damien Breheny; David Thorne (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Alternative fertilization practices lead to improvements in yield-scaled global warming potential in almond orchards - Patrick K. Nichols; Sharon Dabach; Majdi Abu-Najm; Patrick Brown; Rebekah Camarillo; David Smart; Kerri L. Steenwerth (Agriculture, Ecosystems & Environment, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Illegal killing associated with gamebird management accounts for up to three-quarters of annual mortality in Hen Harriers Circus cyaneus - Steven R. Ewing; Cathleen E. Thomas; Nigel Butcher; Blánaid Denman; David J.T. Douglas; David I.K. Anderson; Guy Q.A. Anderson; James Bray; Steve Downing; Ronan Dugan; Brian Etheridge; Will Hayward; et al. (Biological Conservation, 2023)

Wood anatomical and physiological differences between semiarid pine and oak, stand up for their tree ring sensibility to precipitation variability - Ulises Rodriguez-Robles; Tulio Arredondo; David Smart (Agricultural and Forest Meteorology, 2023)

Synsedimentary slump folding: Examples and consequences of an under-recognized process in epicratonic basins - David A. Ferrill; Kevin J. Smart; Daniel J. Lehrmann; Alan P. Morris; Ronald N. McGinnis (Marine and Petroleum Geology, 2023)

Varying response of breeding waders to experimental manipulation of their habitat and predators - David J.T. Douglas; Irena Tománková; Philippa Gullett; Stephen G. Dodd; Daniel Brown; Martin Clift; Norrie Russell; Neal Warnock; Jennifer Smart; Sarah Sanders (Journal for Nature Conservation, 2023)

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Estimating rock mechanical properties from microrebound measurements - Kevin J. Smart; David A. Ferrill; Caroline A. McKeighan; Frederick M. Chester (Engineering Geology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Characterization of a large sex determination region in Salix purpurea L. (Salicaceae) - Ran Zhou; David Macaya-Sanz; Eli Rodgers-Melnick; Craig H. Carlson; Fred E. Gouker; Luke M. Evans; Jeremy Schmutz; Jerry W. Jenkins; Juying Yan; Gerald A. Tuskan; Lawrence B. Smart; Stephen P. DiFazio (Molecular Genetics and Genomics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Bioethanol Production from Brewers Spent Grains Using a Fungal Consolidated Bioprocessing (CBP) Approach - Stuart Wilkinson; Katherine A. Smart; Sue James; David J. Cook (BioEnergy Research, 2017)

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Speleothem constraints on marine isotope stage ( MIS ) 5 relative sea levels, Yucatan Peninsula, Mexico - GINA E. MOSELEY; PETER L. SMART; DAVID A. RICHARDS; DIRK L. HOFFMANN (Journal of Quaternary Science, 2013)
Rates of sea‐level fall at the termination of the last interglacial are poorly defined and archives from which sea‐level elevations are constrained during marine isotope stage (MIS) 5 in the western North Atlantic–Caribbean region are restricted spatially to a few key sites. Here, growth periods of presently submerged but subaerially deposited speleothems from the Yucatan Peninsula, south‐east Mexico, are dated using the 230 Th/ 234 U multi‐collector inductively coupled plasma mass spectrometric method. The growth periods, used to constrain maximum elevations of relative sea level, are in agreement with glacio‐isostatic adjustment models for the near to intermediate region of the former North American ice sheets. Furthermore, our data provide additional constraints on the timing of peak relative sea levels during MIS 5a and 5c, and the timing of the regression following the last interglacial highstand. Combining our data with coral archives of minimum relative sea level from the same region provides a novel approach to calculating the rate of relative sea‐level fall, although initial estimates are poorly constrained because of the wide range in ages observed for the most suitable corals. Copyright © 2013 John Wiley & Sons, Ltd.

Using apparent soil electrical conductivity (ECa) to characterize vineyard soils of high clay content - José Ramon Rodríguez-Pérez; Richard E. Plant; Jean-Jacques Lambert; David R. Smart (Precision Agriculture, 2011)

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain - Edward J. Hodge; David A. Richards; Peter L. Smart; Angel Ginés; David P. Mattey (Journal of Quaternary Science, 2008)
Very few high‐resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub‐millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and δ 13 C of calcite in a Mallorcan stalagmite that grew between 112 and 48 ka. Effective precipitation in Mallorca appears to have been sensitive to proximal sea surface temperature variations and at certain times, ca. 76 ka for example, changed rapidly from moist to arid conditions in only a few centuries. A sea‐level highstand during Marine Isotope Stage (MIS) 5a interrupted growth. Regrowth started promptly after this, but effective precipitation decreased markedly for much of the later part of MIS 5a, and also for shorter periods correlative with Heinrich events H8 (ca. 90 ka) and H6 (ca. 65 ka), with growth ceasing during H5 (ca. 48 ka). Arid episodes in Mallorca appear to be expressions of extremely cold periods recorded further north in Europe and occur contemporaneously with rapid decreases in Greenland temperature. Copyright © 2008 John Wiley & Sons, Ltd.

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Dormant Buds and Adventitious Root Formation by Vitis and Other Woody Plants - David R. Smart; Laszlo Kocsis; M. Andrew Walker; Christine Stockert (Journal of Plant Growth Regulation, 2002)

Population fluctuations and their causes in the African Fish Eagle, (Haliaeetus vocifer (Daudin)) at Lake Naivasha, Kenya - David M. Harper; Maureen M. Harper; Munir A. Virani; Andrew Smart; R. Brooks Childress; Rachel Adatia; Ian Henderson; Bernard Chege (Hydrobiologia, 2002)

Distribution and abundance of the Louisiana red swamp crayfish Procambarus clarkii Girard at Lake Naivasha, Kenya between 1987 and 1999 - David M. Harper; Andrew C. Smart; Stephanie Coley; Sophie Schmitz; Anne-Christine Gouder de Beauregard; Rick North; Chris Adams; Paul Obade; Mbogo Kamau (Hydrobiologia, 2002)

Feeding of the exotic Louisiana red swamp crayfish, Procambarus clarkii (Crustacea, Decapoda), in an African tropical lake: Lake Naivasha, Kenya - Andrew C. Smart; David M. Harper; François Malaisse; Sophie Schmitz; Stephanie Coley; Anne-Christine Gouder de Beauregard (Hydrobiologia, 2002)

Life after lakes: the ecology and management of the water distribution network - Andrew C. Smart; David M. Harper (Hydrobiologia, 1999)